Some Remarks on the Total CR Q and Q′-Curvatures - Marugame, T. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
We prove that the total CR Q-curvature vanishes for any compact strictly pseudoconvex CR manifold. We also prove the formal self-adjointness of the P′-operator and the CR invariance of the total Q′-curvature for any pseudo-Einstein manifold without the assumption that it bounds a Stein manifold.